2019
DOI: 10.24862/cco.v14i2.974
|View full text |Cite
|
Sign up to set email alerts
|

Métodos de sincronização de estro e ovulação em bovinos

Abstract: A Inseminação Artificial em Tempo Fixo (IATF) é uma biotecnologia, que tem possibilitado aos pecuaristas, alcançarem uma alta eficiência reprodutiva do rebanho. Esta biotécnica consiste em sincronizar o ciclo estral de fêmeas bovinas, por meio da aplicação de fármacos análogos aos hormônios naturais em um período pré-determinado. Várias são as metodologias utilizadas para a sincronização do estro e ovulação, como por exemplo, a aplicação sistemática de PGF2α, o protocolo ovsynch e os protocolos a base de proge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…Likewise, Nogueira et al (2016) reported that using FTAI is an excellent tool against the high incidence of postpartum anestrus, it has also become an option to overcome estrus detection in Nellore cows or heifers. Thus, Soares (2019) comments that new estrus synchronization systems (estrus) in cows for AI have been developed using the gonadotropin-releasing hormone (GnRH) available on the market.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, Nogueira et al (2016) reported that using FTAI is an excellent tool against the high incidence of postpartum anestrus, it has also become an option to overcome estrus detection in Nellore cows or heifers. Thus, Soares (2019) comments that new estrus synchronization systems (estrus) in cows for AI have been developed using the gonadotropin-releasing hormone (GnRH) available on the market.…”
Section: Introductionmentioning
confidence: 99%